Supporting Teacher Candidates During COVID-19: Lessons Learned - Atkins, Charlene; Danley, Angela (Educational (Re)naissance, 2020)
This article provides the personal account of two professors who reflect on the challenges of teacher education preparation due to COVID-19. They discuss the swift transition from face to face instruction to virtual learning and teaching including inequities faculty and teacher candidates faced during remote learning, obstacles surrounding state requirements for practicums and certification along with the social emotional impact. Suggestions for moving forward, based on the lessons learned, include additional supports for teacher candidates.